Шлюбні та дітородні орієнтації студентів вищих навчальних закладів м. Києва - Бялковська, В.Г. (Інститут демографії та соціальних досліджень НАН України, 2010)
Статтю присвячено шлюбно-сімейним та дітородним орієнтаціям молоді. В роботі аналізуються дані двох обстежень: “Шлюбні та дітородні орієнтації студентів” та “Сім’я і діти”, які було проведено у квітні 2008 року в Україні. Статью посвящено брачно-семейным и детородным ориентациям молодежи. В работе анализируются данные обследований: “Брачные и детородные ориентации студентов” и “Семья и дети”, проведенных в апреле 2008 года в Украине. The article is devoted matrimonial and childbearing orientation of population in the reproductive age in Ukraine, particularly students of tertiary institutions. We analyzed data from the two special social and demographic sample surveys which were held in April 2008: “Marriage and childbearing preferences of students” and “Family and children”. Unmarried students aged 18-20 years of tertiary institutions of Kyiv were interviewed in the first one. Respondents aged 15-49 years in the survey “Family and children” represented the different groups of population by educational level, status, economic activity and social status. The paper highlights that family-children value stays the main value for respondents. The family with two children is ideal family size by opinions of respondents of different age groups.